p16INK4a Regulates Cellular Senescence in PD-1-Expressing Human T Cells - Janelle, Valérie; Neault, Mathieu; Lebel, Marie-Ève; De Sousa, Dave Maurice; Boulet, Salix; Durrieu, Ludovic; Carli, Cédric; Muzac, Chloé; Lemieux, Sébastien; Labrecque, Nathalie; Melichar, Heather J.; Mallette, Frédérick A.; et al. (Frontiers in Immunology, 2021)
T-cell dysfunction arising upon repeated antigen exposure prevents effective immunity and immunotherapy. Using various clinically and physiologically relevant systems, we show that a prominent feature of PD-1-expressing exhausted T cells is the development of cellular senescence features both in vivo and ex vivo. This is associated with p16INK4a expression and an impaired cell cycle G1 to S-phase transition in repeatedly stimulated T cells. We show that these T cells accumulate DNA damage and activate the p38MAPK signaling pathway, which preferentially leads to p16INK4a upregulation. However, in highly dysfunctional T cells, p38MAPK inhibition does not restore functionality despite attenuating senescence features. In contrast, p16INK4a targeting can improve T-cell functionality in exhausted CAR T cells. Collectively, this work provides insights into the development of T-cell dysfunction and identifies T-cell senescence as a potential target in immunotherapy.